Managing research, development and innovation managing the unmanageable - Jain, Ravi 1935- (Wiley, 2010)
"Managing Research, Development, and Innovation, Third Edition covers the management skills and leadership theories essential to generating products and excelling in today's global economy. Topics of interest include how to design jobs, organize hierarchies, resolve conflicts, motivate employees, and create an innovative work environment. Discover how superior management skills can increase funding, generate profit, and improve the effectiveness of technologically based organizations"--Resource description page.
Includes bibliographical references and index. - Print version record
Keywords: Research, Industrial -- Management; Recherche industrielle; Gestion; BUSINESS & ECONOMICS; Marketing; Research; BUSINESS & ECONOMICS; Research & Development; Research, Industrial; Management